Badania regionalne w historii wychowania - problemy metodologiczne - Glowacka-Sobiech, Edyta (Biuletyn Historii Wychowania, 2008)
The article demonstrates in what way the popularity of the problems of regional studies influences the development of learning (including the history of education), local societies and, paradoxically, the evolution of global history. Additionally, the author of the article gives reasons why the regional studies are becoming more and more popular. One of the reasons, apart from globalization phenomena and the uniting of Europe, is the methodological “revolution” in the field of social sciences, which has significantly altered the research perspective of historians.